Impact of Remittances on Household Income, Asset and Human Capital: Evidence from Sri Lanka - De, Prabal K. (Taylor and Francis, 2013)
This paper explores the developmental impacts of international remittance income on the recipient households. The empirical analysis proceeds in two parts. In the first part, we show that remittance income largely accrues to the families belonging to the bottom quintiles of the income distribution helping the recipient families move up the income ladder. In the second part, we show that remittance income has positive and significant effect on children health and education, but not on conspicuous consumption or asset accumulation. We argue that remittance income is targeted better and not as fungible as other sources of transfer income, as the senders closely monitor it. We use bias-corrected matching estimators to control for self-selection issues.